Vitamin C and E supplementation alters protein signalling after a strength training session, but not muscle growth during 10 weeks of training. (15th December 2014) - Paulsen, G.; Hamarsland, H.; Cumming, K. T.; Johansen, R. E.; Hulmi, J. J.; Børsheim, E.; Wiig, H.; Garthe, I.; Raastad, T.
Abstract : Key points: Although antioxidant supplements are generally believed to give health benefits, recent experiments show that they may adversely affect adaptations to endurance exercise. This study is the first to investigate the effects of high dosages of vitamins C and E on the cellular and physiological adaptations to strength training in humans. Here we report that vitamin C and E supplementation interfered with exercise‐induced signalling in muscle cells after a session of strength training, by reducing the phosphorylation of p70S6 kinase and mitogen‐activated protein kinases p38 and ERK1/2. The vitamin C and E supplement did not significantly blunt muscle hypertrophy during 10 weeks of training; however, some measurements of muscle strength revealed lower increases in the supplemented group than the placebo group. Even though the cellular events are not clearly reflected in physiological and performance measurements, this study implies that redox signalling is important for inducing skeletal muscle adaptations to strength training and that vitamin C and E supplements in high dosages should be avoided by healthy, young individuals engaged in strength training. Abstract: This study investigated the effects of vitamin C and E supplementation on acute responses and adaptations to strength training. Thirty‐two recreationally strength‐trained men and women were randomly allocated to receive a vitamin C and E supplement (1000 mg day −1 and 235 mg day −1, respectively), or a placebo, for 10 weeks. During this period the participants' training involved heavy‐load resistance exercise four times per week. Muscle biopsies from m. vastus lateralis were collected, and 1 repetition maximum (1RM) and maximal isometric voluntary contraction force, body composition (dual‐energy X‐ray absorptiometry), and muscle cross‐sectional area (magnetic resonance imaging) were measured before and after the intervention. Furthermore, the cellular responses to a single exercise session were assessed midway in the training period by measurements of muscle protein fractional synthetic rate and phosphorylation of several hypertrophic signalling proteins. Muscle biopsies were obtained from m. vastus lateralis twice before, and 100 and 150 min after, the exercise session (4 × 8RM, leg press and knee‐extension). The supplementation did not affect the increase in muscle mass or the acute change in protein synthesis, but it hampered certain strength increases (biceps curl). Moreover, increased phosphorylation of p38 mitogen‐activated protein kinase, Extracellular signal‐regulated protein kinases 1 and 2 and p70S6 kinase after the exercise session was blunted by vitamin C and E supplementation. The total ubiquitination levels after the exercise session, however, were lower with vitamin C and E than placebo. We concluded that vitamin C and E supplementation interfered with the acute cellular response to heavy‐load resistance exercise and demonstrated tentative long‐term negative effects on adaptation to strength training.